Neurosurgery Before Science Taking a Chance. - Ganz, Jeremy C. (Cambridge Scholars Publisher, 2021)
It has become increasingly clear that it is easy to misunderstand how surgery functioned in the past. It is all too easy to regard our ancestors as less privileged than ourselves, whereas they were probably every bit as intelligent, but with a different set of priorities. This book traces the development of the profession of surgery and the preoccupations and concerns of its practitioners, from Hippocrates to the early nineteenth century. Topics discussed here include the personal characteristics of surgeons and the regulation of the practice of surgery. The study of anatomy and its limitation.